PENGEMBANGAN PROGRAM KEWIRAUSAHAAN WATER SLIDE DECAL BAGI KEMANDIRIAN BERWIRAUSAHA SISWA SMKN 3 BOYOLANGU KOMPETENSI KEAHLIAN TEKNIK BODI OTOMOTIF - Afandi, Agus; Widiyanti, Widiyanti; Marsono, Marsono (BRILIANT: Jurnal Riset dan Konseptual, 2024)
Vocational High School (SMK) is an appropriate educational institution to develop entrepreneurship education. The development of the concept of learning, continuing, and entrepreneurship (BMW) is a strategy in developing the potential of SMK students to be able to compete globally. However, there are still SMK students, especially TBO graduates in 2023, only 7.9% of 38 students who work according to their expertise competencies. The development of a water slide decal entrepreneurship program is an alternative solution to develop students' potential and skills in entrepreneurship independently. Program development was carried out with the research subject of class XII TBO SMKN 3 Boyolangu. The research design uses the Dick and Carey development model with ten stages, starting from instructional needs analysis to the summative evaluation stage. The development results show that at the expert test stage, the teaching material obtained 93% with a very feasible category, the results of the instructional design expert test 88% with a very feasible category, the results of the small group test obtained 80.3% with a very effective category, and the results of the large group test obtained 83.9% with a very effective category, and the summative evaluation obtained 81% with a very effective category. Based on this exposure, it can be concluded that the implementation of the water slide decal entrepreneurship program development is able to encourage or motivate students in developing an independent spirit of entrepreneurship.